Marijuana use in children: An update focusing on pediatric tetrahydrocannabinol and cannabidiol use. Issue 4 (5th July 2022) - Stoner, Michael J.; Dietrich, Ann; Lam, Samuel Hiu‐Fung; Wall, Jessica J.; Sulton, Carmen; Rose, Emily
Abstract: Cannabis is the most used recreational drug in the United States, and its use is increasing among children and adolescents. With the increase in legalized use, there have been increases in intentional and accidental cannabis exposure in the pediatric population. There is also minimized perceived risk. We review the current use of cannabis and its derivatives, the drug effects and clinical presentation, common misconceptions, pharmacology, and epidemiology. Finally, we review some long‐term consequences of cannabis use.